2020
DOI: 10.3389/fgene.2020.00845
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of mRNA and lncRNA Transcriptomes Reveals the Differentially Hypoxic Response of Preadipocytes During Adipogenesis

Abstract: Zhang et al. Adipocyte Transcriptomes Change After Hypoxia 28 one-to-one lncRNA-mRNA pairs that might be closely related to adipocyte functions, such as ENSCGRT00015041780-Hilpda, TU2105-Cdsn, and TU17588-Ltbp3. These lncRNAs may represent the crucial regulation axis in the cellular response to hypoxia during adipogenesis. This study dissected the effects of hypoxia in the cell during adipogenesis, uncovered novel regulators potentially associated with WAT function, and may provide a new viewpoint for interpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 76 publications
(95 reference statements)
1
3
0
Order By: Relevance
“…The significant upregulation of lncRNA DQ786243 in the intestines of patients with Crohn’s disease suggests that it may play an important role in pathogenesis [ 38 ]. Consistent with previous studies, intestinal lncRNAs showed low expression but high tissue specificity [ 20 ]. Therefore, when evaluating the expression of lncRNAs, we have adopted a lower standard (TPM > 0.1 in at least three samples) than PCGs (TPM > 1 in at least three samples), and we have finally retained 66% (11969/18095) of PCGs and 64% (1701/2634) of lncRNAs.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The significant upregulation of lncRNA DQ786243 in the intestines of patients with Crohn’s disease suggests that it may play an important role in pathogenesis [ 38 ]. Consistent with previous studies, intestinal lncRNAs showed low expression but high tissue specificity [ 20 ]. Therefore, when evaluating the expression of lncRNAs, we have adopted a lower standard (TPM > 0.1 in at least three samples) than PCGs (TPM > 1 in at least three samples), and we have finally retained 66% (11969/18095) of PCGs and 64% (1701/2634) of lncRNAs.…”
Section: Discussionsupporting
confidence: 91%
“…The transcripts per kilobase million (TPM) of PCGs and lncRNAs were calculated by Kallisto (v0.44.0), the parameters of Kallisto use default values. We considering the expression characteristics of different transcripts, the PCGs with TPM > 1 in at least three samples were defined as expressed PCGs (lncRNAs with TPM > 0.1 in at least three samples) [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…was applied to calculate the Pearson correlations between lncRNAs and mRNAs; mRNAs with high correlations (| r | > 0.90 and p < 0.05) were collected ( trans analysis). Finally, the results of cis and trans analysis were integrated to identify one-to-one lncRNA–mRNA pairs ( Zhang et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Because lncRNAs occupy a large part of the human genome in lation of pyruvate to oxaloacetate in order to regulate lipid metabolism (Figure 1C). As adipocytes can be easily isolated and cultured, there are several screening studies to find lncRNAs associated with adipogenesis identifying hundreds of differentially expressed lncRNAs [41][42][43][44][45][46]. Thus, further functional and mechanistic studies are needed to elucidate the functional importance of these adipose-related lncRNAs.…”
Section: Introductionmentioning
confidence: 99%